CARDIOVASCULAR HEALTH SCREENING MANAGEMENT IN PEKANBARU CITY: ANALYSIS OF STRUCTURE, PROCESS, AND BARRIERS - Ardenny Ardenny; Idayanti Idayanti; Ibnu Rusdi (Yayasan Adra Karima Hubbi, 2026)
Cardiovascular disease remains a leading cause of global morbidity and mortality. Cardiovascular health screening programs are essential public health strategies for early identification of heart disease risk. This study aimed to analyze the management of cardiovascular health screening in Pekanbaru City using a mixed-methods approach. Quantitative data were collected from 384 respondents aged 40 years and above, while qualitative data were obtained through in-depth interviews with 21 key informants and focus group discussions with 20 community participants. The results showed extremely low screening coverage (1.82% of the target population of 366,154). Analysis using the Donabedian model identified significant deficits in the structure dimension (only 26.7% of trained health workers, 66.7% of primary health centers lacked cholesterol testing equipment, and minimal budget allocation of Rp 15-25 million/year) and process dimension (absence of standardized SOPs, ineffective risk communication). Bivariate analysis revealed that good knowledge (OR=6.47; p<0.001), close proximity to facilities (OR=2.96; p<0.001), positive attitudes (OR=2.61; p<0.001), and family support (OR=2.27; p<0.001) were significantly associated with screening participation. These findings indicate the need for systematic improvements including capacity building of health workers, provision of adequate equipment, standardization of procedures, and strengthening of risk communication systems to optimize cardiovascular health screening programs in Pekanbaru City.